2000
DOI: 10.1038/modpathol.3880061
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at Codon 72 of p53 Is Not Associated with Cervical Cancer Risk

Abstract: P53 allelic polymorphism at codon 72 has been studied as a possible predisposing factor for cervical carcinogenesis with inconsistent results. Storey and colleagues recently published the interesting finding of a 7-fold increased risk for cervical cancer in women homozygous for the arginine allele at codon 72. This stimulated a number of independent investigations, the majority of which found no association of cervical cancer and arginine homozygosity.With the use of a modified Storey method for determining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
2
11
0
7
Order By: Relevance
“…In Central America, results are available from Mexico, showing a 45% frequency of p53arg (Suarez-Rincon et al, 2002). Against this background, the 67% prevalence of the arg/arg polymorphism in Brazilian women seems to be high, but it is still consistent with the American data reported (Madeleine et al, 2000;Malcolm et al, 2000;Klug et al, 2001;Suarez-Rincon et al, 2002).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In Central America, results are available from Mexico, showing a 45% frequency of p53arg (Suarez-Rincon et al, 2002). Against this background, the 67% prevalence of the arg/arg polymorphism in Brazilian women seems to be high, but it is still consistent with the American data reported (Madeleine et al, 2000;Malcolm et al, 2000;Klug et al, 2001;Suarez-Rincon et al, 2002).…”
supporting
confidence: 80%
“…Similar reports are available on cervical cancer patients from America, suggesting that in South and North America the frequency of p53arg is higher than in Central America. The results of a study carried out in Peruvian women revealed a 50.4% frequency of p53arg (Klug et al, 2001), and in two series of American women, the figures were 55.9% (Madeleine et al, 2000) and 67% (Malcolm et al, 2000), respectively. In Central America, results are available from Mexico, showing a 45% frequency of p53arg (Suarez-Rincon et al, 2002).…”
mentioning
confidence: 99%
“…A histologia é o exame adotado pela maioria dos trabalhos para identificar os casos estudados 2,3,7,15,19 . A formação do grupo controle difere porém de estudo para estudo, mas geralmente considera aquelas pacientes saudáveis com citologia cervical negativa ou sem história de câncer cervical, não se fazendo alusão à colposcopia 4,[20][21][22] .…”
Section: Grupos E Presença De Hpvunclassified
“…Isso porque não só o trabalho de STOREY e colaboradores (1998) mas muitos outros (AGORASTOS et al, 2000;BAEK et al, 2000;BASTIENS et al, 2001;BERTORELLE et al, 1999;DYBIKOWSKA et al, 2000;GIANNOUDIS et al 1999;KIM et al, 2001;LANHAM et al, 1998;MADELEINE et al, 2000;MALCOLM et al, 2000;MINAGUCHI et al, 1998;NGAN et al, 1999;NGAN et al, 2000;NISHIKA W A et al, 2000;PEGO RARO, et al, 2000;PEGORARO, et al, 2002;ROSENTHAL et al, 1998;SARANATH et al, 2002;SKARKA, et al, 1999;SKARKA, et al, 2000;TACHEZY et al, 1999;TENTI et al, 2000;VAN DUIN et al, 2000;YAMASHITA et al, 1999) É interessante ressaltar que os dados observados por todos os trabalhos que apresentaram associação positiva foram obtidos através de PCR alelo-específica (AGORASTOS et al, 2000;DOKIANAKIS et al, 2000;MAKNI et al, 2000;86 PEGORARO et al, 2002;SARANATH et al, 2002;STOREY et al, 1998;VAN DUIN et al, 2000) ou SSCP (Single Strand Conformational Polymorphism) (ANDERSSON et al, 2002;ZEHBE et al, 1999;ZEHBE et al, 2001). Interessantemente, a eficiência de detecção de SSCP vem sendo contestada por trabalhos que compararam os resultados obtidos por esta metodologia com àqueles obtidos por DHPLC (CARGILL et al, 1999e O'DONOVAN et al, 1998.…”
Section: Comparação De Metodologiasunclassified
“…Tem sido relatado que a apoptose dependente de p53, em resposta ao dano no DNA, é independente de síntese de novos RNA ou proteínas (CAELLES et al, 1994 Esses resultados, entretanto, são alvos de grande controvérsia. Um grande número de estudos subseqüente não encontrou a mesma associação (BAEK et al, 2000;BASTIENS et al, 2001;BERTORELLE et al, 1999;CALHOUN et al, 2002;DYBIKOWSKA et al, 2000;GIANNOUDIS et al 1999;GUSTAFSSON et al, 2001;HAYES et al , 1998;HELLAND et al, 1998;HILDESHEIM et al, 1998;JOSEFSSON et al, 1998;KIM et al, 2001;KLAES et al, 1999;KUCERA, et al, 2000;LANHAM et al, 1998;MADELEINE et al, 2000;MALCOLM et al, 2000;MINAGUCHI et al, 1998;NGAN et al, 1999;NGAN et al, 2000;NISHIKA WA et al , 2000;PEGORARO, et al, 2000;REZZA et al, 2001 ;ROSENTHAL et al, 1998;SKARKA, et al, 1999;SONODA et al, 1999;SUAREZ-RINCON et al, 2002;TACHEZY et al, 1999 A amplificação alelo-específica também foi utilizada para identificação deste polimorfismo.…”
unclassified